Drug utilization study in patients of hypertension in tertiary care hospital - Mishra, Prashant S.; Gawali, U. P.; Rizvi, Salman H.; Kaur, Sukhmeen (International Journal of Basic & Clinical Pharmacology, 2020)
Background: Hypertension is the most common modifiable risk factor for cardiovascular diseases, stroke and renal failure. Drug utilization research facilitates the rational use of drugs and provides an insight into the pattern of drug use. As such, the present study was conducted to assess the prescribing patterns of antihypertensive agents and to observe the disparity between the recommended and actual practices for pharmacological management of hypertension at a tertiary care hospital. Methods: A prospective, observational and cross-sectional study was conducted in Department of Pharmacology in collaboration with Department of Medicine in a tertiary healthcare hospital. As per inclusion criteria, patients with hypertension visiting Medicine OPD from 1st October 2018 to 31st December 2018 were enrolled in the study. Results: A total of 390 prescriptions were collected. It was observed that majority of the study patients were female (53.84%) and were >60 years of age. Average number of drugs prescribed per prescription was 4.18. Multiple drug regimen (67.69%) was the mainstay therapy in our study. Prevalence of two drug combination was the highest (46.92%) followed by monotherapy (32.3%). Calcium channel blockers (CCBs) (amlodipine) was the most frequently prescribed class in monotherapy (19.23%). In two drug regimens, the combination of CCB with angiotensin-converting enzyme inhibitors (ACEIs) (combination of amlodipine and enalapril) was prescribed the most (28.46%) whereas prescription of combination of ACEI, beta-blocker (BB) and CCB (enalapril, atenolol and amlodipine combination) was the highest (13.84%) in three drug regimens. Conclusions: The prescription pattern of antihypertensive drugs was found to be rational and mainly in accordance with Joint National Committee VIII guidelines. All the drugs were prescribed by their generic names which suggests awareness among prescribers regarding WHO policies for generic prescribing.